2018
DOI: 10.1186/s13065-018-0418-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of anticancer activity of novel 2-thioxoimidazolidin-4-one derivatives bearing pyrazole, triazole and benzoxazole moieties

Abstract: A novel series of substituted 2-thiohydantoin incorporated with benzoimidazole, pyrazole, triazole and/or benzoxazole moieties has been synthesized using (E)-3-[1-(4-bromophenyl)ethylideneamino]-2-thioxoimidazolidin-4-one 1 as the key starting material. The key material 1 also, reacted with an acetic anhydride, aromatic aldehydes, secondary amines, formaldehyde and triethyl orthoformate to give the corresponding acetyl, chalcone, Mannich bases and ethoxymethylene derivatives, respectively. The structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
(24 reference statements)
1
9
0
1
Order By: Relevance
“…We revealed a cytotoxic and apoptotic effect of compound 4 on a HepG2 cell line. Our results are consistent with a previous study [ 24 ], in which cytotoxicity of some 2-thioxoimidazolidin-4-one derivatives were studied against HepG2 cancer cell line with promising IC 50 values. As a result, apoptosis stimulation is regarded as a critical cellular event that contributes to the therapeutic effectiveness of anti-cancer drugs.…”
Section: Discussionsupporting
confidence: 93%
“…We revealed a cytotoxic and apoptotic effect of compound 4 on a HepG2 cell line. Our results are consistent with a previous study [ 24 ], in which cytotoxicity of some 2-thioxoimidazolidin-4-one derivatives were studied against HepG2 cancer cell line with promising IC 50 values. As a result, apoptosis stimulation is regarded as a critical cellular event that contributes to the therapeutic effectiveness of anti-cancer drugs.…”
Section: Discussionsupporting
confidence: 93%
“…The two signals of the aromatic ring protons showed a doublet in the region of 7.86-7.84 ppm and a multiplet at 7.64-7.03 ppm. The presence of all carbon atoms for compounds 7e-h was con rmed by 13…”
Section: Resultsmentioning
confidence: 90%
“…Authors gratefully thank Central instrument laboratory, University of Tehran for performing 1 H-and 13 C-NMR, FT-IR, mass spectra, and owcytometry experiments analysis. Authors are also grateful to Dr. Ali…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fused pyrazole derivatives showed anticancer activity on human breast cancer (MCF-7) cell lines. [18] Elhady et al, [19] reported the anticancer activity of 2-thioxoimidazolidin-4-one derivatives bearing pyrazole, triazole, and benzoxazole moieties on hepatocellular carcinoma (HepG2) and breast carcinoma (MCF-7) cell lines. Quinolineimidazole derivatives showed antitumor activity on A549 and MCF-7 cell lines with better activity when a bromine atom replaced the C-6 of the quinoline ring.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%